Structural and Vascular Features of Macula Related to the Recurrence of Macular Edema in Central Retinal Vein Occlusion After Anti-VEGF Therapy - Dazhuang Ren; Cece Zhao; Gaoxu Wei; Xiaoyun Hou; Chang Li; Zhiqing Li (Journal of Ophthalmology)
Conclusion: With prolonged CRVO duration, more anti-VEGF injections, and more retinal photocoagulation procedures, retinal, choroidal, and vascular atrophy in the macula occurs in CRVO eyes, making ME less likely to recur. Macular vascular atrophy is vital for the resolution of ME and might be a manifestation of capillary remodeling.